Social and biological evaluation of antimicrobial resistance (SOBEAR) in rural India: a study protocol - Pattnaik, Matrujyoti; Nayak, Ashish Kumar; Karna, Sonam; Rehman, Tanveer; Sahoo, Subrat Kumar; Palo, Subrata Kumar; Kanungo, Srikanta; Kshatri, Jaya Singh; Parai, Debaprasad; Walia, Kamini; Pati, Sanghamitra; Bhattacharya, Debdutta (Frontiers in Public Health, 2024)
Background Antimicrobial resistance (AMR) has been one of the biggest global health threats in recent years, mostly in low- and middle-income countries, which requires urgent research using a multidisciplinary research approach. The use of large quantities of antimicrobial drugs inappropriately for humans, poultry and agriculture has been recognized as a leading cause of antibiotic resistance and the predominance of drug-resistance pathogens in the environment. This protocol aims to describe the use/misuse of antibiotics (ABs) in the community and evaluate clinical samples from healthcare settings to detect genes associated with antimicrobial resistance. Methods We will conduct a community-level survey in different villages of the Tigiria block to assess knowledge and awareness on ABs and AMR. We will conduct in-depth interviews (IDIs) with doctors, pharmacists, nurses and drug sellers, as well as focus group discussions (FGDs) with ASHA and ANM workers who are involved in antibiotic supplies to the community. Quantitative data from the community survey and qualitative data of IDIs and FGDs will be linked and analyzed using statistical modeling and iterative thematic content analysis. Specimens (stool, urine, blood and wound/pus) will be collected from clinically diagnosed patients of different healthcare centers of Tigiria block. The samples will be cultured for bacterial isolation and antibiotic sensitivity testing. Genomic DNA will be isolated from positive bacterial cultures and sequenced using PCR to evaluate high-threat multi-drug resistance organisms (MDROs), screening of plasmid-mediated quinolone resistance (PMQR) genes, antimicrobial genes responsible for MDR and quinolone resistance-determining regions (QRDRs). Conclusion This is the community-based protocol to evaluate the knowledge, attitudes, awareness and practices regarding ABs and AMR. The study protocol establishes a foundation for evaluating population-based prevalence and risk factors for AMR and MDROs in rural areas of the Odisha state, India.